A new species of Ceanothus (Rhamnaceae) from Sierra Madre Occidental, Mexico - Villarreal-Quintanilla, José A.; Estrada-Castillón, Eduardo; Encina-Domínguez, Juan A. (Phytotaxa, 2019)
Ceanothus fernandezii is described as a new species in the subgenus Ceanothus from the Sierra Madre Occidental in the Mexican state of Durango. It differs from known species of Ceanothus for having rigid secondary branches with elliptic to ovate leaves with three veins at the base and a pubescent lower surface, white flowers and smooth fruit. Description, photographs, a key and a distribution map are presented for the new species.